Health claims on foodstuffs: A focus group study of consumer attitudes - Fiona Lalor; Ciara Madden; Kenneth McKenzie; Patrick G. Wall (Journal of Functional Foods, 2011)
Consumers have become increasingly concerned with the foods they eat and the impact they have on their health. To address this, the food industry has developed a wide array of foods that make health claims to reduce disease risk or to improve/maintain a persons’ health. This study was conducted to examine the impact of health claims on peoples’ reactions to these foods. A series of five focus groups involving 35 women were administered. Taste and price were the most influential factors in purchasing foods with health claims. Health claims do influence purchasing in older populations. Mothers of young children are inclined to consider diets which may include foods with health claims. People are positively disposed towards health claims when a friend or relative suffers from a related condition. Many individuals preferred a total diet approach, rather than focusing on individual healthy foods.